Local forage fish abundance influences foraging effort and offspring condition in an endangered marine predator. Issue 7 (20th May 2019) - Campbell, Kate J.; Steinfurth, Antje; Underhill, Les G.; Coetzee, Janet C.; Dyer, Bruce M.; Ludynia, Katrin; Makhado, Azwianewi B.; Merkle, Dagmar; Rademan, Johan; Upfold, Leshia; Sherley, Richard B.
Abstract: Understanding the functional relationship between marine predators and their prey is vital to inform ecosystem‐based management. However, collecting concurrent data on predator behaviour and their prey at relevant scales is challenging. Moreover, opportunities to study these relationships in the absence of industrial fishing are extremely rare. We took advantage of an experimental fisheries closure to study how local prey abundance influences foraging success and chick condition of Endangered African penguins Spheniscus demersus in the Benguela ecosystem. We tracked 75 chick‐provisioning penguins with GPS–time–depth devices, measured body condition of 569 chicks, quantified the diet of 83 breeding penguins and conducted 12 forage fish hydro‐acoustic surveys within a 20 km radius of Robben Island, South Africa, over three years (2011–2013). Commercial fishing for the penguins' main prey, sardine Sardinops sagax and anchovy Engraulis encrasicolus, was prohibited within this 20 km radius during the study period. Local forage fish abundance explained 60% of the variation in time spent diving for 14 penguins at sea within 2 days of a hydro‐acoustic survey. Penguin foraging effort (time spent diving, number of wiggles per trip, number of foraging dives and the maximum distance travelled) increased and offspring body condition decreased as forage fish abundance declined. In addition, quantile regression revealed that variation in foraging effort increased as prey abundance around the colony declined. Policy implications . Our results demonstrate that local forage fish abundance influences seabird foraging and offspring fitness. They also highlight the potential for offspring condition and the mean–variance relationship in foraging behaviour to act as leading indicators of poor prey abundance. By rapidly indicating periods where forage resources are scarce, these metrics could help limit seabird fisheries competition and aid the implementation of dynamic ocean management.